Gender differences in the intention of recent Peruvian medical graduates to emigrate - Pereyra-Elías, Reneé (2013)
Medical emigration is a really important problem for Peru in order to consolidate a sustainable health system. Objectives: To determine the prevalence of emigration intention and associated factors according to gender in recently Peruvian graduated physicians. Design and setting: Cross-sectional, analytic study developed in Lima, Peru in 2010. Participants: Two hundred eightynine recently graduated physicians from Peruvian universities were included. Interventions: An anonymous and auto-administered questionnaire was handed to the study subjects to measure their intention to work abroad. Data was analyzed using the statistical package STATA 11.2, and a log-binomial generalized lineal model was used as regression model for multiple variables. Main outcome measures: Self-reported emigration intention. Results: Prevalence of intended emigration was 42.1%, higher in males (50.0% versus 36.4%; p<0.01). For males, an intermediate/advanced level of English proficiency (PR=1.77; 95%CI: 1.04-2.98) and a monthly income expectation greater than or equal to 3600 U.S. dollars in five years (PR=1.55; 95%CI: 1.09-2.21) were associated with the intention of emigrating. In women there was association with fulfilling the career without delay (PR:1.66; 95%CI: 1.02-2.71) and expectation to win 3600 USD or more in five years (PR:1.71; 95%CI: 1.14-2.57). Conclusions: There was high prevalence of emigration intention in the studied population; the economic factor was associated independently. However, English proficiency and academic regularity differed by gender.